2017
DOI: 10.21873/invivo.11042
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Radiobiological α/β Ratio in Lung Cancer and Fibroblast Cell Lines Using Viability Assays

Abstract: Abstract. Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…If the a/b is further decreased, for a/b~5 Gy the effect found at large a/b values is inverted, and models with decreasing radiosensitivity with increasing fraction size (modified LQ with b < 0 and LQL) become superior to the LQ. Recent estimations of the a/b parameter for early-stage NSCLC from clinical dose response data place its value at around 13 Gy [49], and in vitro studies have also reported a/b ratios above 10 Gy for different lung tumour cell lines [50]. However, a recent work reported lower values (a/b~3 Gy) using a complex mechanistic model [32], while works analysing the clinical reponse of advanced NSCLC have also provided low a/b values (~4 Gy) [51].…”
Section: Discussionmentioning
confidence: 99%
“…If the a/b is further decreased, for a/b~5 Gy the effect found at large a/b values is inverted, and models with decreasing radiosensitivity with increasing fraction size (modified LQ with b < 0 and LQL) become superior to the LQ. Recent estimations of the a/b parameter for early-stage NSCLC from clinical dose response data place its value at around 13 Gy [49], and in vitro studies have also reported a/b ratios above 10 Gy for different lung tumour cell lines [50]. However, a recent work reported lower values (a/b~3 Gy) using a complex mechanistic model [32], while works analysing the clinical reponse of advanced NSCLC have also provided low a/b values (~4 Gy) [51].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, CyberKnife ® SBRT was applied in only two of the considered studies, with a dose range of 13-36 Gy (BED=29.9-79.2, α/β=10). Three fractions were most frequently administered (10/23 treated lesions, 43%) (22,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…The selection of α / β value seems to have no influence on the clinical outcomes in our study; rather it worked just as a scaling factor. Nevertheless, it is important to point out that the selection of α / β value has importance in clinical practice, specifically when performing radiobiological analysis in different cells and tissues, 3 but this was not among the objectives of our study.…”
mentioning
confidence: 99%